PHILOSOPHICAL PERSPECTIVE IN THE FORMATION OF MANAGEMENT PARADIGMS OF HYBRID ORGANIZATIONS - Kiykov, Oleksiy (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2024)
B a c k g r o u n d . The article examines the phenomenon of institutional hybridity in the context of the formation of modern organization management paradigms. Special attention is paid to the philosophical understanding of the interaction of different institutional logics, such as social, commercial, and cultural, which determine the identity and strategies of hybrid organizations. The postmodern approach, which emphasizes ambiguity and complexity, allows us to consider hybrid organizations as adaptive systems that can respond to the rapidly changing conditions of the modern globalized environment. M e t h o d s . This research employed a comprehensive array of methods, including philosophical analysis, comparative method, hermeneutic approach, and literature analysis. The interdisciplinary nature of these methods allowed for a deepened understanding of institutional logic and its pivotal role in shaping the management strategies of hybrid organizations. R e s u l t s . The study showed that combining different institutional logics allows hybrid organizations to balance social and commercial goals through a selective combination of different approaches. Conflicts between logic turned out to be obstacles and potential sources of innovation that contribute to the development of adaptability in management. Hybrid organizations appear as systems constantly in a state of formation, rethinking their identity and mission. C o n c l u s i o n s . Institutional hybridity in managing hybrid organizations is not just a functional requirement, but a conceptual basis for building new management paradigms. A postmodern approach helps organizations integrate different value orientations, ensuring flexibility and resilience in response to external challenges. This creates the basis for developing adaptive management models that consider both pragmatic and ethical requirements.